2020
DOI: 10.1097/md.0000000000019797
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal complications associated with systemic lupus erythematosus

Abstract: Background: Recent guidelines provide better treatment and management of pregnancy in women with systemic lupus erythematosus (SLE). In this analysis, we aimed to systematically assess the maternal and fetal complications associated with SLE using the most recent studies (2017–2019) to obtain an updated result of the present situation. Methods: http://www.clinicaltrials.gov , MEDLINE, Cochrane Central, Web of Science, EMBASE, and Google Scholar were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 19 publications
7
43
1
10
Order By: Relevance
“…Additionally, the PLTC and MNM groups revealed a higher frequency of complications, such as prematurity, stillbirth, miscarriage, neonatal death, low birth weight, and a longer period of hospitalization. We identi ed a high association between SMM and maternal and fetal complications, including low birth weight, neonatal death, fetal loss, and miscarriage, correlating with previous reports [7,[18][19][20][21][22][23]. Prematurity was one of the most signi cant complications, with the majority of pregnancies in the MNM group delivering earlier than 27 weeks (71.5%), with statistically signi cant increased risk of preterm delivery in both MNM and PLTC groups.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, the PLTC and MNM groups revealed a higher frequency of complications, such as prematurity, stillbirth, miscarriage, neonatal death, low birth weight, and a longer period of hospitalization. We identi ed a high association between SMM and maternal and fetal complications, including low birth weight, neonatal death, fetal loss, and miscarriage, correlating with previous reports [7,[18][19][20][21][22][23]. Prematurity was one of the most signi cant complications, with the majority of pregnancies in the MNM group delivering earlier than 27 weeks (71.5%), with statistically signi cant increased risk of preterm delivery in both MNM and PLTC groups.…”
Section: Discussionsupporting
confidence: 83%
“…The caesarean section surgery was accepted by 34 (61.8%) patients in our study. The absolute rate was surprisingly high in both groups, and it was much higher than that reported in most previous studies, but lower than that of another Chinese study [15,20]. SLE was still a risk factor for maternal and fetal outcomes.…”
Section: Discussioncontrasting
confidence: 67%
“…Although the overall risk of PB was similar to other studies, 2 , 24 we found a higher risk for PB (45%) and lower birth weight when anti-CD20 mAb was given during pregnancy. This might be partially related to the underlying disease and/or concomitant autoimmune diseases, 25 especially in NMOSD, to the previous DMT exposure and/or other concomitant medication with steroids, and deserves further investigation. To what extent long-term treatment with anti-CD20 mAbs may lead to hypogammaglobulinemia, which in turn could increase the risk of neonatal and maternal infections 26 , 27 including chorioamnionitis—another potential underlying mechanism of PB—is still unknown.…”
Section: Discussionmentioning
confidence: 99%